Studies on Haemato-Biochemical Findings in Hypothyroid Dogs - Nagella, Naveen; Rani, N Lakshmi; Reddy, K Basava; Prasad, V Devi (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Hypothyroidism is an endocrine disorder due to diminished synthesis and secretion of triiodothyronine (T3) and thyroxine (T4) by the thyroid glands. The present study was carried out at Veterinary Clinical Complex, NTR College of Veterinary Science, Gannavaram during the period from March 2023 to November 2023. The hospital prevalence of hypothyroidism in the present study was found to be 0.45 per cent (27/5957). The mean TT4 (7.74±0.60 nmol/L) and FT4 (0.32±0.04 ng/dL) in hypothyroid dogs was significantly (p ≤0.01) lower when compared to healthy dogs. Haemato-biochemical changes included significantly (P
Keywords: hypothyroidism; thyroxine; hypercholesterolemia; hypertriglyceridemia; radioimmunoassay